2017
DOI: 10.1111/apha.12997
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the functional role of microRNA‐214‐3p in atherosclerosis for the identification of novel targeted therapies to prevent or reverse endothelial cell dysfunction and stimulate autophagy

Abstract: L. 2017. MicroRNA-214-3p: a link between autophagy and endothelial cell dysfunction in atherosclerosis. Acta Physiol 222, e12973.The original article by Wang et al., entitled "MicroRNA-214-3p: A Link between Autophagy and Endothelial Cell Dysfunction in Atherosclerosis," brings new data concerning molecular mechanisms linking decreased autophagy to endothelial dysfunction in atherosclerosis. In this issue of Acta Physiologica, the authors concluded that microRNA-214-3p (miR-214-3p) controls oxidized low-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The miR‐214 level was significantly lower in coronary artery disease patients compared with that in controls, which may be a biomarker for alerting severe coronary artery disease 24 . Also, miR‐214‐3p was downregulated in HAECs stimulated with ox‐LDL 25,26 …”
Section: Discussionmentioning
confidence: 95%
“…The miR‐214 level was significantly lower in coronary artery disease patients compared with that in controls, which may be a biomarker for alerting severe coronary artery disease 24 . Also, miR‐214‐3p was downregulated in HAECs stimulated with ox‐LDL 25,26 …”
Section: Discussionmentioning
confidence: 95%
“…Wang et al recently observed a novel link between decreased stress‐related autophagy and endothelial dysfunction in atherosclerosis, mediated by miR‐214‐3p …”
mentioning
confidence: 99%
“…Therefore, a thorough understanding of the potential pathophysiological mechanisms involving the above factors is of great importance for the development of novel therapeutic strategies in atherosclerosis (Brown et al, 2016). Recently, microRNA (miRNA)targeted therapies are proposed to limit the morphology of atherosclerotic plaque and reverse the dysfunction of endothelial cells, thus, to prevent the progression of atherosclerosis (Georgescu, 2018;Lovren et al, 2012).…”
mentioning
confidence: 99%